Microstructure Properties of Popular Alkali-Activated Pastes Cured in Ambient Temperature - Muralidhar Kamath; Shreelaxmi Prashant; Rahul Ralegaonkar (Buildings, 2023)
This paper reported on the micro-level properties of alkali-activated pastes cured in ambient conditions. The mechanisms influencing setting time and the microstructure development of fly ash, slag, and metakaolin were studied. The mortar compressive strength of the binders and their ultrasonic pulse velocity (UPV) were tested after 56 days of ambient curing. The micro-level properties of paste cured at ambient conditions for seven days were determined to understand the phases developed. NASH gel was observed to delay setting and possessed lower compressive strength, while CASH gel was set early and possessed high compressive strength. The micro-characterisation of the alkali-activated binder system developed with fly ash and metakaolin showed the presence of NASH gel. The alkali-activated binder system developed with GGBS contained multiple gels, such as N, C-ASH, and CSH. The molecular structures of CSH, CASH, NASH, and N, C-ASH are also presented and were obtained using high score plus software.